Enhancing Pronunciation Skills of Intermediate Students Through Computer Assisted Language Learning (CALL) - Muhammad Nasir,; Fehmina Nazar,; Muhammad Kamran Abbas,; Abdul Waheed,; Javed Ahmad, (Al-Qanṭara, 2023)
The present study aims to enhance the pronunciation skills of intermediate students through Computer Assisted Language Learning (CALL). The present research study is experimental in its nature and uses both qualitative and quantitative approaches to make the comprehension better. Controlled and experimental group design is highly encouraged in social sciences. Data collection was carried out through pre-test and post-test. Data was analyzed through SPSS. In Pakistan, teachers are reluctant to adopt technology which results in the demotivation of the students towards English language. The researcher has implemented pre-test and post-test. The students were divided into controlled and experimental groups. Experimental group was taught pronunciation through CALL which results in the enhanced score as well as a positive attitude towards CALL. The findings of this research study show that CALL offers students a variety of learning approaches and that they value it highly meant that students were extremely motivated. Students did not rely substantially on their teachers. Through CALL, the current study was effective in improving intermediate students' pronunciation. This study is also efficacious in identifying improvements in the students' motivation and pronunciation.